The Impact of Internet on Research -A Case Study on Master Students at Economics & Administration College in King Abdul-Aziz University - Obaid, Rawia Reda; Alamoudi, Hind Ahmed; Alreheli, Ghaidaa Sultan; Abu Rizaiza, Lujain Asad (Journal of Humanities & Social Sciences, 2023)
This study aims to identify the impact of using the Internet while holding scientific researches. Indeed, this study surveys the opinions of a sample of male and female master’s students in the College of Economics and Administration at King Abdul Aziz University for the year 2020. This study relies on the descriptive analytical method, which is appropriate to the nature of such researches. The research sample was selected using the non-probability sampling method (soft sampling), The study sample consisted of (35) male and female students out of (350), meaning that the study sample represented 10% of the study population. In light of the results analysis, the researchers find several results, and the most important results are: Most of the sample members agree on the positive effect of using the Internet while holding scientific researches. Indeed, there are many advantages to using the Internet while holding scientific researches which include, the ease and speed of obtaining the information, and the low cost of obtaining that information. On the other hand, there are some obstacles to using the Internet while holding scientific researches which are: the difficulty of ascertaining that the information available on the Internet is credible, and the possibility of deleting the information sources from the internet. In light of these results, the researchers agree on the importance of holding training courses for graduates of King Abdul Aziz University on how to benefit from the Internet in the field of scientific research. Also, the researcher must ensure the credibility of the information on the Internet; Because it is possible for anyone to upload information on the Internet, it is possible that there is incorrect information.